Minimally Invasive Transforaminal Lumbar Interbody Fusion: Meta-analysis of the Fusion Rates. What is the Optimal Graft Material?. Issue 6 (17th April 2017) - Parajón, Avelino; Alimi, Marjan; Navarro-Ramirez, Rodrigo; Christos, Paul; Torres-Campa, Jose M; Moriguchi, Yu; Lang, Gernot; Härtl, Roger
Abstract: BACKGROUND: Minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) is an increasingly popular procedure with several potential advantages over traditional open TLIF. OBJECTIVE: The current study aimed to compare fusion rates of different graft materials used in MIS-TLIF, via meta-analysis of the published literature. METHODS: A Medline search was performed and a database was created including patient's type of graft, clinical outcome, fusion rate, fusion assessment modality, and duration of follow-up. Meta-analysis of the fusion rate was performed using StatsDirect software (StatsDirect Ltd, Cheshire, United Kingdom). RESULTS: A total of 1533 patients from 40 series were included. Fusion rates were high, ranging from 91.8% to 99%. The imaging modalities used to assess fusion were computed tomography scans (30%) and X-rays (70%). Comparison of all recombinant human bone morphogenetic protein (rhBMP) series with all non-rhBMP series showed fusion rates of 96.6% and 92.5%, respectively. The lowest fusion rate was seen with isolated use of autologous local bone (91.8%). The highest fusion rate was observed with combination of autologous local bone with bone extender and rhBMP (99.1%). The highest fusion rate without the use of BMP was seen with autologous local bone + bone extender (93.1%). The reported complication rate ranged from 0% to 35.71%. Clinical improvement was observed in all studies. CONCLUSION: Fusion rates are generally high with MIS-TLIF regardless of the graft material used. Given the potential complications of iliac bone harvesting and rhBMP, use of other bone graft options for MIS-TLIF is reasonable. The highest fusion rate without the use of rhBMP was seen with autologous local bone plus bone extender (93.1%).